1995
DOI: 10.1161/01.cir.92.10.2819
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Antithrombin Activity of Low-Molecular-Weight Heparins

Abstract: Our results provide an explanation for the effectiveness of LMWHs administered either once or twice daily. High and sustained plasma antithrombin activity is achieved when LMWHs are administered in therapeutic doses used in contemporary trials with only a moderate prolongation of the aPTT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…They compared the relative half-lives of prophylactic and therapeutic doses of LMWH by assessing both antiIIa and anti-Xa activity. In contrast to the other studies, which reported a low half-life of the anti-IIa activity, they found that a high and sustained plasma anti-IIa activity was achieved when LMWH were administered in therapeutic doses used in contempo rary trials with only a moderate prolongation of the APTT [27].…”
Section: Low Molecular Weight Heparins (Lmwh)contrasting
confidence: 81%
“…They compared the relative half-lives of prophylactic and therapeutic doses of LMWH by assessing both antiIIa and anti-Xa activity. In contrast to the other studies, which reported a low half-life of the anti-IIa activity, they found that a high and sustained plasma anti-IIa activity was achieved when LMWH were administered in therapeutic doses used in contempo rary trials with only a moderate prolongation of the APTT [27].…”
Section: Low Molecular Weight Heparins (Lmwh)contrasting
confidence: 81%
“…30 However, this assay still reflects only one part of a patient's coagulation system, more precisely one anticoagulant factor. Apart from factor Xa, proteins like antithrombin also inhibit other proteins of the coagulation system, such as thrombin, 31 factor VIIa, 32 factor IX, 33 and contact pathway factors. 34 Assays known to assess interactions in the coagulation system more holistically are viscoelastic whole blood tests, often used as point-of-care (POC) devices.…”
Section: Discussionmentioning
confidence: 99%
“…Low-molecular-weight heparins offer high and sustained plasma antithrombin activity when administered in therapeutic doses, with only moderate prolongation of the activated partial thromboplastin time [21]. Low-molecular-weight heparins have pharmacokinetic advantages over unfractionated heparin [22], as detailed in table 4.…”
Section: Optimal Anticoagulant Regimenmentioning
confidence: 99%